2010
DOI: 10.1038/ajg.2010.216
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Ductopenia and Treatment Response Predict Long-Term Histological Progression in Primary Biliary Cirrhosis

Abstract: Patients with PBC who fail to show a biochemical response to UDCA or who have ductopenia on baseline biopsy progress histologically during extended follow-up. Such patients may benefit from novel treatments, with our exploratory data providing a means of identifying these individuals early in their disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
267
3
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(284 citation statements)
references
References 25 publications
10
267
3
4
Order By: Relevance
“…They estimate the risk of LT or death (overall death for the GLOBE score and liver‐related death for the UK‐PBC risk score) in patients with PBC at specific time points. Both scores outperformed previous response criteria7, 8, 9, 10, 11, 13, 14 in terms of prognostic utility and could potentially help physicians identify patients at high risk of disease progression and in need of second‐line therapy. They have also been validated in patients not treated with UDCA, strongly suggesting that such scoring systems reflect disease activity and stage expressed by the laboratory investigations, regardless of treatment.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…They estimate the risk of LT or death (overall death for the GLOBE score and liver‐related death for the UK‐PBC risk score) in patients with PBC at specific time points. Both scores outperformed previous response criteria7, 8, 9, 10, 11, 13, 14 in terms of prognostic utility and could potentially help physicians identify patients at high risk of disease progression and in need of second‐line therapy. They have also been validated in patients not treated with UDCA, strongly suggesting that such scoring systems reflect disease activity and stage expressed by the laboratory investigations, regardless of treatment.…”
mentioning
confidence: 93%
“…These patients experience progressive liver disease that may eventually lead to liver failure or hepatocellular carcinoma 6. It is well established that the liver biochemistry on treatment with UDCA strongly predicts long‐term outcomes in PBC 7, 8, 9, 10, 11. The response to treatment with UDCA (so‐called UDCA response) may therefore be defined in terms of the liver biochemistry measured at a specific time (usually 12 months) after starting treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, given the known protracted clinical course of early stage PBC, a much longer follow-up would be necessary to demonstrate survival benefit in this population. Since then, numerous observational studies from Europe and North America have shown that treatment with UDCA is associated with excellent survival free of LT, especially patients with early histological stage and who have biochemical response to UDCA (143,(148)(149)(150)(151) . The decline in number of patients receiving liver transplant for PBC in Europe and North America is seen as further evidence of the survival benefit provided by long-term use of UDCA in PBC (152,153) .…”
Section: Treatment With Ursodeoxycholic Acidmentioning
confidence: 99%
“…These patients have poorer prognosis (147)(148)(149) . Ductopenia, advanced histological stages (stages III and IV) and moderate-severe interface hepatitis, bilirubin > 1 mg/dL, low serum albumin levels, portal hypertension and the Mayo risk score are all pre-treatment factors associated with poorer response to UDCA and poorer overall prognosis (146)(147)(148)(149)151,155) . As PBC characteristically affects women older than 40 years of age, pregnancy is not common after the diagnosis.…”
Section: Treatment With Ursodeoxycholic Acidmentioning
confidence: 99%